Simulation and Optimization of a Naphtha Thermal Cracking Pilot Plant - Mohammad Shahrokhi; Mir Esmaeil Masoumi; Mojtaba Sadrameli; Jafar Towfighi Darian (Iranian Journal of Chemistry & Chemical Engineering, 2003)
In thermal cracking plants, it is desired to apply an optimal temperature profile along the reactor to minimize the operation cost. In this article a simulator is developed by the use of a mathematical model, which describes the static operation of a naphtha thermal cracking pilot plant. The model is used to predict the steady state profiles of the gas temperature and product yields. Using a dynamic programming technique, an optimal temperature profile along the reactor is obtained. The effects of operating variables such as steam to hydrocarbon ratio (S/HC), coil outlet temperature (COT) and feed flow rate on product yield are investigated. Pilot plant simulation results are compared with the industrial data and the results indicate that they follow the same trend.